Laughter in the Isaac Narrative: Who Has the Last Laugh? - Vorchheimer, Hannah (Iggrot Ha'Ari, 2023)
This article tackles the question of the nature of Sarah’s laughter. It argues that it is imperative to go beyond labeling the laughter as either incredulous or joyous, as it is a reductive approach. The nuanced approach of this paper appreciates the “both and-ness” of the laughter demonstrating its larger significance in the Genesis narrative.